The genomic analysis of a wide peach germplasm collection revealed genetic relationships between European landraces and American ferals and landraces - Aballay, Maximiliano Martín; Ksouri, Najla; Valentini, Gabriel Hugo; Puebla, Andrea Fabiana; Gogorcena Aoiz, Yolanda; Sanchez, Gerardo (ISHS, 2023)
The advance of next generation sequencing (NGS) technologies allows the implementation of high-throughput genotyping at a reasonable cost. This open the possibility to learn more about phylogenetic relationships, genetic variability, and the development of new genetic markers for breeding purposes. In this work a previous developed ddRAD-seq platform was applied for the genotyping of two peach collections curated at the EEA San Pedro (237 genotypes) and the EE Aula Dei (89 genotypes). Here we present a joint analysis of a total of 798×106 of paired-end (2×250 bp) reads belonging to 326 genotypes (2,45M reads genotype-1). A total of 564,382 SNPs were discovered and a reduced data set composed of 10,576 SNP (MAF >1% and missing data <10%) was used in a combination of analyses (principal component analysis, population structure and phylogeny). The results showed that the ancestral germplasms differ largely from modern peach cultivars. In addition, genetic relationships between American landraces (North American and Bolivian), American ferals (Argentinian) and European landraces (Spanish and Italian) were revealed suggesting a common origin which probably reflect the introduction of germplasm by the Spaniards during the colonization period. These results with some outstanding traits of ancestral genotypes (fruit quality, high yield/vigour, pathogen resistance, thermal requirements, etc.) encourage the usage of this germplasm on breeding programs for the development of new varieties with agricultural impact.